Effect of Coating Composition on the Alkali Resistance of Galvalume Anti - Finger Coatings for Buildings - SONG Ming - juan (Cailiao Baohu)
Anti - finger coated Galvalume panels for construction have high alkaline resistance requirements, but there are few reports on this. Through adjusting the composition of the anti - finger coating, the influence of the coating on the alkaline resistance to Galvalume anti - finger coating for buildings was studied by 5% NaOH drop test. Results showed that the formula design and monomer selection of the water - based resin as the coating bonding skeleton played a decisive role in the alkali resistance of the fingerprint - resistant coating. The softened lubricating additive during the baking - curing process had a sealing effect, which made the fingerprint coatings have more resistance to alkali corrosion. Besides, the use of anionic / nonionic in lubricant additives had better alkaline resistance. When the film - forming agent had low boiling points or rapid volatility, this would lead to the poor continuity and uniformity of anti - finger coatings, presenting poor alkaline resistance. On the contrary, if the film - forming agent had a high boiling point or slow volatilization, the coating exhibited good alkali resistance after drying.